Willingness-to-pay and preferences for warfarin pharmacogenetic testing in Chinese warfarin patients and the Chinese general public. (March 2013) - Chan, Sze Ling; Wen Low, Joshua Jun; Lim, Yee Wei; Finkelstein, Eric; Farooqui, Muhammad Assad; Chia, Kee Seng; Wee, Hwee Lin
Aim: Genetic factors have been found to affect warfarin maintenance dose and a key factor for the successful clinical implementation of warfarin pharmacogenetic testing (WPGT) is economic sustainability. We aimed to estimate the willingness-to-pay (WTP) and preferences for WPGT in Singaporean Chinese subjects.Methods & subjects: A total of 197 warfarin patients and 187 members of the public completed a questionnaire. The discrete choice methodology was used and the choice model was estimated using hierarchical Bayes. Marginal WTP, attribute importance and WTP for three hypothetical WPGTs were calculated from the estimated utilities.Results: Both patients and the public placed most emphasis on side effects, followed by cost, number of International Normalized Ratio tests and 'nature of test'. WTP for WPGT ranged from S$160 to S$730.Conclusion: WPGTs are likely to be economically sustainable.